Outreach cataract surgery services: how good are their outcomes? - Nieder-Heitmann, Norman (Division of Ophthalmology, 2020)
Background Cataracts are the main cause of blindness worldwide. Cataract blindness is reversible with surgery, a procedure which is well recognized for its clinical and cost effectiveness. Several approaches are used to reduce the cataract burden. They include a “reach out” approach, a “reach in” approach and a combination of the two. The Aravind Eye Care System in India, performing over 250 0000 cataract surgeries annually, exclusively utilizes the “reach in” approach. In neighbouring Nepal, with its large rural population residing in mountainous areas, outreach services still play an essential role in addressing cataract blindness. In South Africa, there are several non-governmental cataract surgery services utilizing the “reach out” approach. Objectives The primary objective of this study is to investigate the visual outcomes of a nongovernmental organization providing outreach cataract surgery services (referred to as the “Outreach Service” from now on) in South Africa. This was done by directly comparing them to the visual outcomes obtained at a permanent hospital-based cataract surgery service. The secondary objective is to compare the visual outcomes in both these settings to the recommended day one postoperative visual acuities as set out by the WHO. Methods A retrospective comparison was made of the day one postoperative visual acuities of patients who underwent cataract surgery during outreaches conducted by the Outreach Service and the day one postoperative visual acuity of patients who were operated on at Groote Schuur Hospital. The study period was from July 2014 to December 2014. Results A total of 1067 cases from the Outreach Service and 584 cases from Groote Schuur Hospital were included in the study. The patients who underwent surgery at Groote Schuur Hospital had significantly better day one visual acuities (Pearson chi square test, p< 0.0001). The day one visual acuity in cases performed during outreaches also did not fulfil the minimum day one visual acuity as set out by the World Health Organization (WHO). Conclusion Despite its limitations, our study does raise concerns about the quality of cataract surgery performed on these outreaches. Our recommendation is that non-governmental outreach cataract surgery services should audit their four to six-week visual outcomes. Should they still not meet the WHO’s criteria, the necessary steps should be taken to identify and rectify the reasons for these poor outcomes. Ultimately, South Africa should strive towards establishing more permanent eye care centres.